2009
DOI: 10.1007/s10008-008-0778-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical codeposition of nickel oxide and polyaniline

Abstract: The morphologies and elemental components of the films were inspected by Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Diffraction (EDX). The stability of nickel oxide in the films was found to be enhanced against acidic environments. Electrochemical catalytic behavior of NiO x within the composite film was conserved and demonstrated by catalytic oxidation of methanol and ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…the methanol concentration dependency of R ct are further tted to eqn (25) to estimate the values of the rate constants. From this equation values of the rate constants k 1 ¼ 3.86 s À1 , k À1 ¼ 0.31 s À1 and k 2 ¼ 1.24 Â 10 3 cm 3 mol À1 s À1 have been calculated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the methanol concentration dependency of R ct are further tted to eqn (25) to estimate the values of the rate constants. From this equation values of the rate constants k 1 ¼ 3.86 s À1 , k À1 ¼ 0.31 s À1 and k 2 ¼ 1.24 Â 10 3 cm 3 mol À1 s À1 have been calculated.…”
Section: Resultsmentioning
confidence: 99%
“…The use of alkaline solutions in a fuel cell has many advantages such as increasing its efficiency, 4,5 a wider selection of possible electrode materials, a higher efficiency of both anodic and cathodic processes, almost no sensitivity to the surface structure 6 and negligible poisoning effects in alkaline solutions were observed. [24][25][26][27][28][29][30][31] Moreover, the possibility of dispersing metallic particles inside the polymers gives electrodes with higher surface areas, enhanced electrocatalytic activities and facilitates electron transfer due to semiconducting properties 29 and a change in the Fermi level towards the oxidation of organic molecules. As described previously, 9,10 a considerable increase in power density and fuel utilization was obtained by optimizing different components of fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…Such activity can be synergistically combined with that of the immobilized inorganic NPs, as shown in the following examples. different fuels, such as methanol [251], ethanol [251,252], and also polyhydroxyl compounds [250] were tested on NiO x -containing CP electrodes. In all the cases the M a n u s c r i p t studied, and the Fe 3 O 4 /PPy hybrid showed 7.5 times larger catalytic activity compared to neat PPy [45,46].…”
Section: Heterogeneous (Photo-)catalysismentioning
confidence: 99%
“…Subsequently, both components, and therefore the hybrid itself is electrogenerated in the same process in one single step. This approach have been exploited to obtain hybrids with PPy, PEDOT, and most importantly PANI; containing Fe 2 O 3[242], MnO 2[243][244][245][246][247][248], MoO 3[249], NiO x[250][251][252], and WO 3[253,254]. The main advantage of this approach is its simplicity and time efficiency.…”
mentioning
confidence: 97%
“…Due to the improvement of conductivity, the film has good electrochemical properties. To further confirm that the NiO addition can improve the properties of PANI, Peng [29] theoretically studied the electrochemical properties of PANI/NiO composites, who believed that the structure and distribution pattern of NiO are critical for effectively improving the specific capacitance of PANI. Although the above studies have confirmed that PANI/NiO has good electrochemical properties, its fabrication as electrode materials with good cycling performance for flexible supercapacitor application has never been reported.…”
Section: .Introductionmentioning
confidence: 97%